Direct and quasi-direct band gap of novel Si-Ge alloys in P-3m1 phase. (22nd July 2021) - Fan, Qingyang; Hao, Bingqian; Yang, Fang; Song, Yanxing; Yu, Xinhai; Yun, Sining
Abstract: This work investigates the crystal structure, stability, mechanical properties, electronic properties, effective masses, and optical properties of Si-Ge alloys in the P -3 m 1 phase. The elastic constants and phonon spectra proven that the Si-Ge alloys in the P -3 m 1 phase have mechanical and dynamic stability. The bulk modulus, shear modulus and Young's modulus of Si-Ge alloys in the P -3 m 1 phase decrease with the increase of Ge composition, and the three-dimensional diagram of Young's modulus and effective mass show that the mechanical and transport properties have anisotropy. The Si12 Ge12 in the h P24 phase is a quasi-direct band gap semiconductor material with a band gap of 1.081 eV, while the Si30− x Ge x alloy ( x = 6, 12, 18, 24) in the h P30 phase are all direct band gap semiconductor materials with the band gaps of 0.541 eV, 0.430 eV, 0.561 eV, and 0.387 eV, respectively. The h P30-Si6 Ge24 has a very small effective electron mass. The h P24-Si12 Ge12 show excellent absorptive capacity in the visible and infrared region region. Based on this work, Si-Ge alloys in the P -3 m 1 phase are promising materials for photovoltaic applications.